Quantifying cell free DNA in urine: comparison between commercial kits, impact of gender and inter-individual variation. (25th May 2018) - Streleckiene, Greta; Reid, Hayley M; Arnold, Norbert; Bauerschlag, Dirk; Forster, Michael
DNA can enter the blood circulation from living cells by extracellular vesicles or at cell death, and pass into urine through the kidney barrier. Urine can be collected non-invasively, making it an interesting source of cell-free DNA (cfDNA) for research studies and ultimately for clinical diagnostics. However, there is currently a lack of data on the quantity and variability of cfDNA in urine. Here, we benchmark two commercial urine cfDNA isolation kits with respect to the quantity of DNA, the labor time, and cost. The results show distinctive differences between each kit. Furthermore, the cfDNA amount from the same probands varied strongly from day to day and may be higher in female samples than in male samples (p = 0.003).